ยุทธศาสตร์และโมเดลพันธกิจเพื่อพัฒนามหาวิทยาลัยวิจัยสู่มหาวิทยาลัยเชิงประกอบการ - อวิรุทธ์ ฉัตรมาลาทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The purposes of this research are to 1) study the concept and operations of entrepreneurial universities 2) study the current state and needs of developing research universities toward entrepreneurial universities 3) analyze the success factors of developing research universities toward entrepreneurial universities 4) propose the strategies and mission model for developing research universities toward entrepreneurial universities. The samples include 1) 6 experts on entrepreneurial universities 2) 209 faculty and institute administrators of research universities 3) 9 policy-level administrators of research universities 4) 5 executives of government sector 5) 5 executives of business-industry sector and 6) 9 experts for connoisseurship discussion. The research instruments include the content analysis form, interview forms, questionnaire, and form for validation of (draft) strategies and mission model. Meanwhile, the content analysis, frequency, percentage, mean, standard deviation, and priority need index are used in the data analysis. The research results can be summarized as follows: 1. The entrepreneurial university is the university with the mindset of entrepreneurship as the basis of culture and management. The operations focus on 1) leadership and governance, 2) organizational capacity, 3) teaching and learning for entrepreneurship development, 4) pathways to entrepreneur, 5) university and external sectors relationship for knowledge exchange, 6) internationalization and 7) measuring the impact of the entrepreneurial university. 2. The current state and needs of developing research universities toward entrepreneurial universities are found that overall current state is at the intermediate level. The aspect of entrepreneurial university values has the highest level of mean and the aspect of measuring the impact of the entrepreneurial university has the lowest level of mean. Meanwhile, the first priority need is measuring the impact of the entrepreneurial university, the second priority need is teaching and learning for entrepreneurship development, the third priority needs are organizational capacity and university and external sectors relationship for knowledge exchange. 3. The success factors of developing research universities toward entrepreneurial universities consist of 1) entrepreneurship education 2) understanding 3) good practices 4) internal collaboration 5) external collaboration 6) entrepreneurial organization culture 7) research in responding to social and economic needs 8) rules and regulations and 9) infrastructure and information technology. 4. The proposed strategies and mission model for developing research universities toward entrepreneurial universities comprise the vision, missions, 4 strategic themes "EPIC". The themes include 1) Entrepreneurship Education 2) Shared Value Partnership 3) Ecosystem & Entrepreneurial Innovation and 4) Entrepreneurial Organization Culture. There are 12 goals, 20 tactics, 46 indicators, 62 projects/activities and 9 components of mission model.